Bioactivity of Farnesyltransferase Inhibitors Against Entamoeba histolytica and Schistosoma mansoni - Probst, Alexandra; Nguyen, Thi N.; El-Sakkary, Nelly; Skinner, Danielle; Suzuki, Brian M.; Buckner, Frederick S.; Gelb, Michael H.; Caffrey, Conor R.; Debnath, Anjan (Frontiers in Cellular and Infection Microbiology, 2019)
The protozoan parasite Entamoeba histolytica can induce amebic colitis and amebic liver abscess. First-line drugs for the treatment of amebiasis are nitroimidazoles, particularly metronidazole. Metronidazole has side effects and potential drug resistance is a concern. Schistosomiasis, a chronic and painful infection, is caused by various species of the Schistosoma flatworm. There is only one partially effective drug, praziquantel, a worrisome situation should drug resistance emerge. As many essential metabolic pathways and enzymes are shared between eukaryotic organisms, it is possible to conceive of small molecule interventions that target more than one organism or target, particularly when chemical matter is already available. Farnesyltransferase (FT), the last common enzyme for products derived from the mevalonate pathway, is vital for diverse functions, including cell differentiation and growth. Both E. histolytica and Schistosoma mansoni genomes encode FT genes. In this study, we phenotypically screened E. histolytica and S. mansoni in vitro with the established FT inhibitors, lonafarnib and tipifarnib, and with 125 tipifarnib analogs previously screened against both the whole organism and/or the FT of Trypanosoma brucei and Trypanosoma cruzi. For E. histolytica, we also explored whether synergy arises by combining lonafarnib and metronidazole or lonafarnib with statins that modulate protein prenylation. We demonstrate the anti-amebic and anti-schistosomal activities of lonafarnib and tipifarnib, and identify 17 tipifarnib analogs with more than 75% growth inhibition at 50 μM against E. histolytica. Apart from five analogs of tipifarnib exhibiting activity against both E. histolytica and S. mansoni, 10 additional analogs demonstrated anti-schistosomal activity (severe degenerative changes at 10 μM after 24 h). Analysis of the structure-activity relationship available for the T. brucei FT suggests that FT may not be the relevant target in E. histolytica and S. mansoni. For E. histolytica, combination of metronidazole and lonafarnib resulted in synergism for growth inhibition. Also, of a number of statins tested, simvastatin exhibited moderate anti-amebic activity which, when combined with lonafarnib, resulted in slight synergism. Even in the absence of a definitive molecular target, identification of potent anti-parasitic tipifarnib analogs encourages further exploration while the synergistic combination of metronidazole and lonafarnib offers a promising treatment strategy for amebiasis.